Anthropometry profile and pattern of gadget playing activity for preschoolers - Hidasari, Fitriana Puspa; Bafadal, Muhammad Fachrurrozi (Journal Sport Area, 2021)
Gadget can cause sedentary behavior that can affect motor skills and pointedly as one of the contributing factors to anthropometry. The research objective is to identify anthropometric profiles and device use activities in early childhood. The research method used is descriptive quantitative. The sampling technique used is purposive sampling and found 862 samples. The instrument in this study uses digital scale, stature meter and questionnaire. Data processing is using Microsoft Excel 2010 and the WHO Anthro Software. The results show that 40.49% of children used gadgets for more than 60 minutes per day and 59.51 are under 60 minutes per day. The pattern of playing gadgets shows 38.40% for games and 61.60% watching videos via YouTube. The anthropometric profile found children with very thin 1.97%, 16.00% thin, 66.36 normal, 5.34 fat, and 10.33 obese. In terms of height, it is found that 1.99% has a very short posture, 7.60% short, 84.01% normal, and 5.70% tall. Based on nutritional adequacy, there are 11.48% under nutrition, 75.17% good nutrition, and 13.35% over nutrition. The conclusions of this study are that most of the anthropometric profiles of children in Pontianak city are still in the normal category but there is an increasing trend in the number of children who fall into the categories of overweight, obesity, over nutrition, and short posture. This study also finds that as many as 40.49% of children are passively using devices in the form of watching YouTube videos and playing games with a duration not recommended by the World Health Organization (WHO) and the American Academy of Pediatrics (AAP).